Implementation of Technology-Based Interactive Learning Media in Supporting Students’ Learning Motivation - Ummu Salma; Haris Habibul Fattah; Eko Setiawan; Ika Ratih Sulistiani (Jurnal Inovasi Pendidikan dan Sains, 2025)
The decline in learning motivation in Islamic Religious Education (PAI) learning has become a tangible challenge, particularly when the material is delivered conventionally without considering the characteristics of the digital generation. This study specifically aims to explore the implementation of technology-based interactive learning media, reveal the effect of technology-based interactive learning media on students’ learning motivation, and identify supporting and inhibiting factors in the implementation of technology-based learning in PAI subjects at SMPI Salafiyah Singosari. The approach used was qualitative with a case study method, conducted through observation, interview, and documentation techniques. The research results show that the implementation of technology-based interactive learning media at SMPI Salafiyah Singosari is carried out in a planned manner through the use of Quizizz, Wordwall, animated videos, and interactive PowerPoint aligned with the MerdekaCurriculum. The implementation of interactive learning media has a positive effect on students’ learning motivation, as evidenced by increased attention, active participation, self-confidence, and satisfaction in PAI learning. The success of the implementation is supported by teacher readiness, school infrastructure, and student enthusiasm. At the same time, the main obstacles include limited digital devices, disparities in access among students, and the technical burden on teachers in preparing the media. These findings indicate that technology-based interactive media is effective in creating adaptive and participatory PAI learning